Strategi Pengembangan UMKM Dengan Inovasi Kemasan dan Branding di Desa Karya Maju, Kecamatan Tanjung Pura, Kabupaten Langkat - Nurroyian, Nurroyian; Wulandari, Latifah; Siregar, Efrina Reza Amanda; Ikhsan, Muhammad; Milhan, Milhan (Jurnal Abdi Mas Adzkia, 2024)
This community engagement program aims to bridge the development gap of UMKM (Micro, Small, and Medium Enterprises) in Karya Maju Village, Tanjung Pura District, Langkat Regency, and significantly enhance the competitiveness of local products. Utilizing a participatory action research (PAR) approach within the Real Work Lecture (KKN) program of the State Islamic University of North Sumatra (UINSU), this project involves students in designing logos, creating banners, and assisting with the digital registration of UMKM products. The program addresses the challenges of branding and limited digitalization faced by UMKM, particularly their reliance on traditional marketing and lack of consistent visual identity. Data were collected through direct observation, in-depth interviews, and documentation of production processes, packaging techniques, and branding practices. The program was conducted in three stages: participatory planning, action implementation, and collaborative evaluation. Results indicate that the introduction of logos, banners, and modern packaging significantly improved the visibility of UMKM products and enhanced consumer perception. Moreover, participants reported increased motivation to adopt branding strategies and explore digital marketing platforms. However, limitations such as unfamiliarity with online tools and lack of advanced digital devices were identified as areas requiring further intervention. This study concludes that simple, participatory interventions in branding and packaging can create sustainable improvements in the competitiveness and marketability of UMKM products. Future programs should focus on digital literacy training and broader scalability to ensure long-term impact.